Is the fact that other people believe in God a reason to believe? Remarks on the Consensus Gentium Argument. - Dobrzeniecki, Marek (European journal for philosophy of religion, 2018)
According to The Consensus Gentium Argument from the premise: Everyone believes that God exists one can conclude that God does exist. In my paper I analyze two ways of defending the claim that somebody's belief in God is a prima facie reason to believe. Kelly takes the fact of the commonness of the belief in God as a datum to explain and argues that the best explanation has to indicate the truthfulness of the theistic belief. Trinkaus Zagzebski grounds her defence on rationality of epistemic trust in others. In the paper I argue that the second line of reasoning is more promising and I propose its improved version.